TRANSFORMATION AS THE CHURCH'S EFFORTS TO OVERCOME POVERTY IN INDONESIA BASED ON PSALM 146:1-10 - Sihotang, Henriko (CV. AFDIFAL MAJU BERKAH, 2023)
In this case the author proposes a solution based on Psalm 146:1-10, namely that the church carries out transformation as an effort to overcome major problems in Indonesia. The method used is qualitative research which includes library research with critical historical theory, namely form criticism (sitz im leben). The Psalms were sung in communion with the nation of Israel. In particular, surah 146 is read to strengthen the hope that humans will only believe in Allah, while rejecting the power of the nobles. The nobles mentioned by the Psalmist had various unavoidable weaknesses, referring to their limitations. The psalmist reminds us again that the God in question is the God of Jacob. God is almighty and remains faithful in fulfilling His covenant, namely liberation. God will save everyone who asks for His help like one of human ancestors, Jacob. The psalmist praises that as God freed Jacob, so God also freed the Israelites from oppression. In Israel's history, God's submission was manifested through Israel's kings. God chose the kings of Israel to be tools or agents to carry out God's plan or vision of liberation. The novelty of this research is that churches in Indonesia with real commitment will be able to solve the big problem, namely poverty in Indonesia. Likewise, churches in the world will be able to solve global problems. This church-centered approach relies on the church's ability to fight poverty more effectively than other institutions. The church is an institution that has the resources to provide solutions to big problems. By mobilizing churches in all corners of Indonesia, churches can reach communities and the specific needs of the poor